2019
DOI: 10.29252/ibj.23.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression Profile of ZFX Variants Discriminates Breast Cancer Subtypes

Abstract: Background: ZFX is a transcriptional regulator in embryonic stem cells and plays an important role in pluripotency and self-renewal. ZFX is widely expressed in pluripotent stem cells and is down-regulated during differentiation of embryonic stem cells. ZFX has five different variants that encode three different protein isoforms. While several reports have determined the overexpression of ZFX in a variety of somatic cancers, the expression of ZFX-spliced variants in cancer cells is not well-understood. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Yang et al (2020) found augmented expression of ZFX in EC tissues (Yang et al, 2021). The same expression tendency of ZFX has also been reported by Pourkeramati et al (2019) who unraveled increased ZFX levels in breast cancer tissues (Pourkeramati et al, 2019). Functionally, elevated ZFX levels resulted in active pancreatic cancer cells and accelerated tumor growth in vivo (Song et al, 2018).…”
Section: Discussionsupporting
confidence: 61%
“…Yang et al (2020) found augmented expression of ZFX in EC tissues (Yang et al, 2021). The same expression tendency of ZFX has also been reported by Pourkeramati et al (2019) who unraveled increased ZFX levels in breast cancer tissues (Pourkeramati et al, 2019). Functionally, elevated ZFX levels resulted in active pancreatic cancer cells and accelerated tumor growth in vivo (Song et al, 2018).…”
Section: Discussionsupporting
confidence: 61%